Search in leptonic channels for heavy resonances decaying to long-lived neutral particles - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; et al. (2013)
A search is performed for heavy resonances decaying to two long-lived massive neutral particles, each decaying to leptons. The experimental signature is a distinctive topology consisting of a pair of oppositely charged leptons originating at a separated secondary vertex. Events were collected by the CMS detector at the LHC during pp collisions at √s = 7 TeV, and selected from data samples corresponding to 4.1 (5.1) fb-1 of integrated luminosity in the electron (muon) channel. No significant excess is observed above standard model expectations, and an upper limit is set with 95% confidence level on the production cross section times the branching fraction to leptons, as a function of the long-lived massive neutral particle lifetime. Copyright CERN.